Strategies for the Synthesis of the Halenaquinol and Xestoquinol Families of Natural Products - Schwarzwalder, Gregg M.; Vanderwal, Christopher D. (European journal of organic chemistry, 2017)
The halenaquinol family of naphthoquinol natural products includes a few closely related polycyclic compounds that each feature an activated, electrophilic furan ring. This motif is likely responsible for the rich biological activity attributed to these secondary metabolites. Their interesting structures – related through their electrophilic furan moieties to the biologically important furanosteroids – and their activities prompted significant efforts by organic chemists that resulted in many strategically compelling laboratory syntheses of these targets. These different strategies are compared and contrasted in this microreview, and the authors' recent work on the structurally different but biogenetically related natural product exiguaquinol is put into the context of the previous studies on halenaquinol‐type targets. The wealth of different strategies for the chemical synthesis of the halenaquinol/xestoquinol family of natural products is discussed. Similar themes throughout the different achievements are highlighted, and a discussion of the recently discovered relative exiguaquinol is included.